NOVA1-Mediated SORBS2 Isoform Promotes Colorectal Cancer Migration by Activating the Notch Pathway - Zhang, Tao; Chen, Sixia; Peng, Yi; Wang, Changgang; Cheng, Xi; Zhao, Ren; Liu, Kun (Frontiers in Cell and Developmental Biology, 2021)
Background: Gene expression and alternative splicing (AS) could promote cancer development via a complex mechanism. We aimed to identify and verify the hub AS events and splicing factors associated with colorectal cancer (CRC) progression. Methods: RNA-Seq data, clinical data, and AS events of 590 CRC samples were obtained from the TCGA and TCGASpliceSeq databases. Cox univariable and multivariable analyses, KEGG and GO pathway analyses were performed to identify hub AS events and splicing factor/spliceosome genes, which were further validated in 5 CRCs. Results: In this study, we firstly compared differentially expressed genes and gene AS events between normal and tumor tissue. Differentially expressed genes was different from genes with differentially expressed AS events. Prognostic analysis and co-expression network analysis of gene expression and gene AS events were conducted to screen 5 hub gene AS events involved in CRC progression: EPB41L2, CELF2, TMEM130, VCL, SORBS2. By qRT-PCR, we also verified that the gene AS events SORBS2 were downregulated in tumor tissue, and gene AS events EPB41L2, CELF2, TMEM130 and VCL were upregulated in tumor tissue. The genes whose mRNA levels were significantly related the 5 hub gene AS events were significantly enriched in the GO term of cell division and Notch signaling pathway. Further co-expression of gene AS events and alternative splicing factor genes revealed NOVA1 as the crucial factor regulating the hub gene AS event expression in CRC. By in vitro experiments, we found that NOVA1 inhibited gene AS event SORBS2, which induced migration of CRC cells via Notch pathway. Conclusion: Integrated analysis of gene expression and gene AS events and further experiments revealed NOVA1-mediated SORBS2 promoted migration of CRC, which indicated a potential therapeutic target.